Adverse Events Following Cancer Immunotherapy: Obstacles and Opportunities - Pauken, Kristen E.; Dougan, Michael; Rose, Noel R.; Lichtman, Andrew H.; Sharpe, Arlene H. (Trends in immunology, 2019)
Oncology has recently undergone a revolutionary change with widespread adoption of immunotherapy for many cancers. Immunotherapy using monoclonal antibodies against checkpoint molecules, including programmed death (PD)-1, PD ligand (PD-L)1, and cytotoxic T lymphocyte-associated antigen (CTLA)-4, is effective in a significant subset of patients. However, immune-related adverse events (irAEs) have emerged as frequent complications of checkpoint blockade, likely due to the physiological role of checkpoint pathways in regulating adaptive immunity and preventing autoimmunity. As immunotherapy becomes more common, a better understanding of the etiology of irAEs and ways to limit these events is needed. At the same time, studying these new therapy-related disorders provides an opportunity to better understand naturally occurring human autoimmune and inflammatory disorders, with the potential to improve therapies for cancer and autoimmune diseases. IrAEs represent a major obstacle for safely administering checkpoint blockade in cancer patients. Developing methods to minimize irAEs while maintaining effective antitumor immunity could make immunotherapy safer for more cancer patients. Diverse mechanisms likely drive irAEs, which may share varying degrees of similarities and differences with spontaneous autoimmunity. IrAEs that develop following checkpoint blockade in cancer provide an opportunity to better understand spontaneous autoimmune and inflammatory disorders. A deeper understanding of why some patients develop irAEs and others do not is needed to determine who is at highest risk for developing life threatening irAEs and to develop biomarkers to identify these individuals. Improvements in managing, investigating, and reporting on these irAEs are needed to reduce clinical challenges and maximize opportunities to learn from irAEs.